Membangun Mental Entrepreuner Guna Persaingan Bisnis di Bidang Konveksi Pada Pelaku Usaha di Konveksi Angkola Jaya Tapanuli Selatan - Nasution, Nazaruddin; Azhar, Intan Nisa (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
One of the components in the Tridharma of Higher Education is carrying out community service activities. Every lecturer has an obligation to carry out community service which aims to share the knowledge possessed to support the progress of society. Implementation of community service in this activity. This study aims to build the mentality of an entrepreneur in business competition to the level of sales of convection products in the South Tapanuli region. This service activity is also in line with government programs that encourage the progress of small and medium enterprises. The target of this activity is the community, business actors and employees at the Angkola Jaya Convection. This service program is carried out for 1 day (August 5, 2020). The method used is to provide training on the influence of electronic media on the marketing of products. The results of this service indicate that the participants are very enthusiastic in participating in the training so that they can build entrepreneurial mentality in facing business competition in their business.